(3eHGOF GOGQI GdNWQ hGdJGejfs - (3eMeO Jhajb(B, (3GdHdbjfjs ((3GdbGgQI(B:s (3OGQ GdcJH GdGcGOjejI(B,s, 2003)
...(3jeKd Shb GdJCejf LRAkG gGekG heJcGedkG ef GdShb GdeGdjI(B.. (3Hd jYJHQ bWGY GdJCejf ef Cge GdbWGYGJ GdeGdjI hGdJLGQjI eMdjkG hOhdjkG, hjYJHQ bWGY GdJCejf aj eUQ ef Cge GdeDKQGJ aj GdShb GdeGdjI, hdbO MOK JWhQkG hGSY GdfWGb aj Shb GdJGejf HeUQeeKdkG aj XghQ hGfJTGQ cGaI CfhGY GdJZWjGJ GdJCejfjI ShGA cGfJ JCejfGJ CTNGU Gh JCejfGJ eeJdcGJ Ch JCejfGJ ELHGQjI(B. (3ceG JeKd Pdc GdJhSY aj JfhY hGfJTGQ GdgjFGJ GdbGFeI Ydi JbOje GdNOeI GdJCejfjI abO XgQ aj Shb GdJCejf GdeUQj GdYOjO ef TQcGJ GdJCejf ShGAkG cGfJ TQcGJ bWGY CYeGd YGe, Ch bWGY CYeGd NGU, gPG HGdEVGaI Edi GdgjFGJ GdbhejI hGdMchejI ddJCejf(B. (3hdPdc cGf dRGekG Ydi GdLgGJ GdYdejI aj eUQ Gf JbOe GdeRjO ef GdJYQja hGdOQGSI HgPG GdMbd GdgGe aj Shb GdeGd hGdJLGQI, HMjK jSJjWY GdehGWf Cf jNOe GdeLJeY GdeUQj aj gPG GdeLGd, hceSGgeI efG jSYOfG Cf fOe gPG GdcJGH eJVefkG JYGQja hOQGSI hGajI HeHGOF GdNWQ hGdJCejf ef GdfGMjJjf GdfXQjI hGdJWHjbjI, hbO Je YQV gPG GdcJGH ef NdGd SJI CHhGH hge cGdJGdj(B: ((3GdHGH GdChd(B: (3OQGSI GdLhGfH GdYdejI hGdYedjI aj GdNWQ, GdHGH GdKGfj(B: (3OQGSI ebOeI fXQjI Yf GdJCejf, GdHGH GdKGdK(B: (3OQGSI GdLhGfH GdYdejI hGdYedjI daQhY GdJGejfGJ GdYGeI, GdHGH GdQGHY(B: (3OQGSI GdLhGfH GdYdejI hGdYedjI aj aQhY GdJCejf Ydi GdMjGI, GdHGH GdNGeS(B: (3OQGSI GdLhGfH GdYdejI hGdYedjI aj GdJCejfGJ GdELJeGYjI, GdHGH GdSGOS(B: (3OQGSI GdLhGfH GdYdejI hGdYedjI aj EYGOI GdJCejf(B).s
(3HjHdjhZQGajG (B: (3U(B. 715s
Keywords: (3EOGQI GdCReGJs; (3EOGQI GdeNGWQs; (3GdJCejf(B-(3eNGWQs